Association between breakfast consumption pattern with body mass index (bmi) and physical activity among undergraduate students in Universiti Sains Malaysia, Health Campus, Kubang Kerian, Kelantan. - Zulkifflee, Iwani Afifah (Universiti Sains Malaysia, 2024)
Breakfast is widely acknowledged as the most important meal of the day because it provides energy throughout the day and offers many benefits, including physical, mental, and cognitive functions. However, the practice of healthy eating habits, such as consuming breakfast, is still reported to be low among young adults, especially university students. Therefore, this study aimed to determine the association between breakfast consumption pattern with body mass index (BMI) and physical activity among undergraduate students at the USM Health Campus, Kubang Kerian, Kelantan. This cross-sectional study involved 116 undergraduate students selected through a convenience sampling method. The self-administered questionnaire consisted of four sections: socio-demographic characteristics, anthropometric measurements, the International Physical Activity Questionnaire (IPAQ), and questions related to breakfast consumption patterns. The majority of respondents were female (81.0%), aged between 19 and 23 years (90.5%) with a mean age of 21.90 ± 1.40 years. Most respondents were third-year students (32.8%), PPSK students (87.1%), and of Malay ethnicity (64.7%). More than half of respondents, 58.6%, spent between RM10 to RM15 on their daily food budget, with a mean of RM14.66 ± 6.03 and received between RM500 to RM1000 for their monthly allowance, with mean of RM553.73 ± 261.78. A total of 38.8% received loans as sponsorship throughout their studies and 97.4% of the respondents stayed in campus hostel. Based on BMI classification, 11.2% were underweight, 43.9% were normal weight, 29.3% were overweight, and 16.4% were obese. Regarding physical activity levels, 45.7% had moderate physical activity levels, and 55.2% of respondents were classified as breakfast skippers. However, there was no significant association between breakfast consumption patterns and BMI (p= 0.267). The findings also revealed that there was no significant association between breakfast consumption patterns and physical activity reported in this study (p= 0.279).